The Influence of Health Education on the Knowledge of Hypertension in Riverbank Communities - Lola Illona Elfani Kausar; Gt. Khairunnisa; Muhammad Lukman; Retny Zulhijati Mala; Muhammad Harrisfadillah (GLOBAL HEALTH SCIENCE GROUP, 2026)
Hypertension is often called a silent killer because it usually does not show early signs, but can cause serious complications and even death. In Indonesia, the prevalence of hypertension reaches 34.1%, and South Kalimantan is recorded as the province with the highest figure at 44.1% with the working area of the West Martapura Community Health Center being one of the areas with the most cases where the majority of the population lives on the riverbanks. The habit of consuming salted fish with high sodium content and the low public understanding of hypertension are factors that worsen public health conditions. How the influence of health education can increase the knowledge of people living on riverbanks regarding hypertension. This was a quasi-experimental study using a one-group pretest–posttest model. Thirty respondents were selected using purposive sampling. The research instrument was a hypertension knowledge questionnaire in accordance with the theory. Univariate and bivariate analyses were performed using the Wilcoxon test. The majority of respondents were female (77%), had an elementary school education (46%), and worked as housewives (50%). The average knowledge score increased from 79.33 to 86.33 after the intervention. The Wilcoxon test showed a significant increase in knowledge (p = 0.010). Health education is effective in increasing the knowledge of hypertension in riverside communities. Regular health education is recommended as a promotional and preventive measure for at-risk groups.